Investments in education for trade - Edmund Köhn (Intereconomics, 1974)
In spite of its importance for the economy, trade in developing countries has been falling short of the attention it deserves in discussions about development policies. It is all the more necessary, therefore, henceforth to make the very existence, and the increasing use, of trade consulting services part and parcel of development strategy.
Keywords: 330; Development Policy